TINJAUAN SINGKAT OPTIMALISASI PEMANFAATAN ENERGI SURYA PADA SEKTOR RUMAH TANGGA - Ligan Budi Pratomo; Nazaruddin Sinaga (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2022)
Energy use always increases, especially fossil energy. Through the National Energy Policy, the government continues to strive to increase the role of new and renewable energy sources so as to reduce dependence on fossil energy. Solar power generation is a type of renewable energy generator that capable to convert solar energy to electric energy. The main components of solar power generatios are batteries, solar panels, charger controllers, and inverters. Solar power generations technology itself is always being developed, such as automatic monitoring and sun tracking systems designed to improve system performance. One of the applications of solar power generations is in the household sector. In this sector consumes 49% of the national electricity energy in 2018. This type of generator is categorized as a roof solar power generations. Based on existing data, there were 1400 roof solar power generations users in September 2019. The development of solar energy utilization for the household sector is very appropriate because it can help achieve renewable energy about 23% in 2025 and 31% in 2050 in the national energy mix.